m-deferred statistical convergence of order a - Temizsu, F.; Et, Mikail; Çınar, Muhammed (University of Nis, 2016)
In this paper, we introduce the concepts of ?m-deferred statistical convergence of order ? and strong ?mr-deferred Cesàro summability of order ? of real sequences. Additionally, some inclusion relations about ?m-deferred statistical convergence of order ? and strong ?mr- deferred Cesàro summability of order ? are given. © 2016, University of Nis. All rights reserved.
Keywords: (?m-deferred statistical convergence; Strong ?m-deferred Cesàro summability